Evaluation of the surface microhardness of composite resins. Literature review. (International Journal of Medical and Surgical Sciences, 2017)
At present, the use of composite resins has increased considerably, becoming the main restorative material used by dentists, both for the anterior and posterior sectors. Among its properties, we find the hardness, which is a very important part to determine its durability in the mouth. This property is determined by the amount of filler that the resin presents, therefore, the greater the amount of filler, the greater its hardness and smaller dimensional changes. Despite all the improvements in technology and properties of composite resins, there is still no material that has ideal characteristics that make it indestructible over the years. The objective of this article is to review the main characteristics of composite resins, especially surface microhardness. Hardness is a condition of the surface of a given material, it does not represent any property of the material and is related to the elastic and plastic properties of each material. There are currently many systems to measure hardness, for example, Brinell, Rockwell, Vickers and Knoop systems.
Keywords: composite resins; surface microhardness; dental restoration